2014
DOI: 10.1038/emi.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

A gorilla reservoir for human T-lymphotropic virus type 4

Abstract: Of the seven known species of human retroviruses only one, human T-cell lymphotropic virus type 4 (HTLV-4), lacks a known animal reservoir. We report the largest screening for simian T-cell lymphotropic virus (STLV-4) to date in a wide range of captive and wild non-human primate (NHP) species from Cameroon. Among the 681 wild and 426 captive NHPs examined, we detected STLV-4 infection only among gorillas by using HTLV-4-specific quantitative polymerase chain reaction. The large number of samples analyzed, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
(112 reference statements)
1
27
0
1
Order By: Relevance
“…Further screening did not reveal STLV-2 in monkeys from DRC. Similarly, STLV-4 was recently identified in gorillas (LeBreton et al 2014), but was not observed in NHP from our study. Prevalences varied also per species, ranging here from 5% in De Brazza and wolf's monkeys to 40% in Allen's swamp monkeys.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Further screening did not reveal STLV-2 in monkeys from DRC. Similarly, STLV-4 was recently identified in gorillas (LeBreton et al 2014), but was not observed in NHP from our study. Prevalences varied also per species, ranging here from 5% in De Brazza and wolf's monkeys to 40% in Allen's swamp monkeys.…”
Section: Discussionsupporting
confidence: 68%
“…The four HTLV types, 1 to 4, in humans have each simian counter-parts (STLV-1 to 4) (Le Breton et al 2014; Gessain 2011; Gessain et al 2013). HTLV-1 and 2 are relatively widespread and are estimated to infect around 20 million people, but HTLV-3 and HTLV-4 have only been documented in a handful of indivuduals in central Africa (Gessain et al 2012; Mahieux et al 2011; Richard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] As well, PREDICT researchers found strong evidence for western lowland gorillas (Gorilla gorilla gorilla) as the nonhuman primate reservoir for Human T-lymphotropic virus in western Africa, and discovered a new simian immunodeficiency virus strain in a naturally infected chimpanzee (Pan troglodytes troglodytes) with AIDS-like symptoms. 25,26 Hepatitis B virus (HBV) was found to be circulating among gorillas and chimpanzees and among subspecies of chimpanzees, refuting the previously held assumption that HBV genotypes are host-specific, with implications for the potential for spillover in this group of viruses. 27 Furthermore, PREDICT documented anthropozoonoses-human to primate transmission of viruses-including a human metapneumovirus that caused fatal respiratory disease in wild mountain gorillas (Gorilla beringei beringei) and human herpes simplex-1 virus that caused classic stomatitis in confiscated eastern lowland gorillas (Gorilla beringei graueri).…”
Section: Wildlife Surveillance At Human-wildlife Interfacesmentioning
confidence: 94%
“…A decade later, some cases of humans carrying HTLV-3 and 4 were also described in Cameroon, and although the epidemiology of these two viruses has not been fully studied, it is hypothesized that they might be widespread in Central Africa, although with low prevalence rates [128,129]. Finally in 2014, STLV-4, the simian counterpart of HTLV-4, was described in a gorilla from Cameroon [130]. Genetic homology of HTLV-3 and 4 with HTLV-1 is high, as they share the same gene structure (gag, pro, pol, env, tax and rex genes), suggesting that these viruses might also share the same pathogenicity mechanisms and routes of transmission [131].…”
Section: Htlv-3 and Htlv-4mentioning
confidence: 98%